In vitro evaluation of 2-methoxyestradiol-bis-sulphamate on cell growth, morphology, cell cycle progression and its possible induction of types of cell deaths in an oesophageal carcinoma (SNO) cell line - Joubert, Annie M. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.